2018
DOI: 10.18632/oncotarget.24873
|View full text |Cite
|
Sign up to set email alerts
|

Glypican-1 is enriched in circulating-exosomes in pancreatic cancer and correlates with tumor burden

Abstract: BackgroundGlypican-1 (GPC1) is expressed in pancreatic ductal adenocarcinoma (PDAC) cells and adjacent stromal fibroblasts. Recently, GPC1 circulating exosomes (crExos) have been shown to be able to detect early stages of PDAC. In this study, we investigated the usefulness of crExos GPC1 as a biomarker for PDAC.MethodsPlasma was obtained from patients with benign pancreatic disease (n = 16) and PDAC (n = 27) prior to pancreatectomy, and crExos were isolated by ultra-centrifugation. Protein was extracted from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(105 citation statements)
references
References 24 publications
5
100
0
Order By: Relevance
“…As such, exosomes from the serum of patients emerged as an attractive approach to possibly detect cancerous lesions and monitor and predict outcome of cancer patients. Several studies have reproduced our original findings related to enrichment of GPC1 in cancer exosomes, including in breast cancer exosomes, colorectal, esophageal and pancreas cancer [2][3][4][5]8,[18][19][20] (Table 1). Additionally, most of these reports show that such enrichment of GPC1 in exosomes can serve as biomarker.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…As such, exosomes from the serum of patients emerged as an attractive approach to possibly detect cancerous lesions and monitor and predict outcome of cancer patients. Several studies have reproduced our original findings related to enrichment of GPC1 in cancer exosomes, including in breast cancer exosomes, colorectal, esophageal and pancreas cancer [2][3][4][5]8,[18][19][20] (Table 1). Additionally, most of these reports show that such enrichment of GPC1 in exosomes can serve as biomarker.…”
Section: Introductionsupporting
confidence: 70%
“…In the last two years, GPC1 detection on cancer exosomes has been demonstrated by several different independent studies. Such validation included breast cancer cellsderived exosomes and colorectal and esophageal cancer-derived exosomes, in addition to exosomes analyzed from pancreatic cancer cases [2][3][4][5]8,14,[18][19][20] (Table 1). Despite employing different methodologies and approaches, GPC1 was reported as elevated in exosomes of patients with different cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TMB is correlated with clinical outcome in multiple cancer types treated with CPI (65,66). Previous studies indicated that TMB levels correlated with gene mutations in tumors (25,40,67,68). TMB-H has been reported to correlate with the generation of neoantigens and potential clinical responses to immunotherapies (69).…”
Section: Discussionmentioning
confidence: 99%
“…Newly found biomarkers such as AHNAK2 or THBS2, which are potentially successful diagnostic markers, need to be involved in studies to show their effects in screening programs [84,85,86]. Additionally, biomarkers like Glypican-1, CD63, and miR-451a exosomes seem to be promising [87,88,89]. Nevertheless, in the development of successful biomarkers, it needs to be noted that predispositions such as chronic pancreatitis and pancreatic cancer may have different genetic abnormalities [90].…”
Section: Procedures Of Screeningmentioning
confidence: 99%